Status Goods : Experimental Evidence from Platinum Credit Cards - Bursztyn, Leonardo; Ferman, Bruno; Fiorin, Stefano; Kanz, Martin; Rao, Gautam (World Bank, Washington, DC, 2017)
This paper provides novel evidence on status goods, using a series of field experiments with an Indonesian bank that markets platinum credit cards to high-income customers. In a first experiment, the paper shows that demand for the platinum card greatly exceeds demand for a nondescript control product with identical benefits, suggesting demand for the pure status aspect of the card. Transaction data reveal that platinum cards are more likely to be used in social contexts, implying social image motivations. Combining price variation with information on the use of the card sheds light on the magnitude of the demand for social status. A second experiment provides evidence of positional externalities from the consumption of these status goods. The final experiment shows that increasing self-esteem causally reduces demand for status goods. This suggests that part of the demand for status is psychological in nature, and that social image is a substitute for self-image.